PREFERENSI NYAMUK Aedes sp. DAN Culex sp. MENGGUNAKAN MEDIA CAIR LIMBAH RUMAH TANGGA DI BANJARBARU - Hasnawiyah Qudsi (Bioscientiae, 2012)
The aim of this study is to assess the preferences of Aedes sp and Culex sp onbreeding place using wastewater of rice and liquid soap waste. This study used purposivesampling method, the sample taken from yard of 6 villages in the district of North andsouth Banjarbaru. Sample taking by placing the sample retrieval ovitrap containing wasteliquid soap, sewage wastewater of rice and water wells. The number of larvae obtained inliquid soap waste media for Aedes sp is up to 3140 and Culex sp larvae is up to 67 larvae,while the wastewater of rice for Aedes sp amounted to 1863 larvae and Culex spamounted to 1539 larvae. t test showed that the effect of liquid soap waste andwastewater of rice against Aedes sp and Culex sp larvae are different but not real. Wasteliquid soap and wastewater of rice favored by Aedes sp and Culex sp larvae, so, both thewaste liquid soap and wastewater of rice can be used as breeding media for Aedes sp. andCulex sp.